PERAN TEKNOLOGI DIGITAL DALAM MEMFASILITASI PEMBELAJARAN JARAK JAUH SELAMA PANDEMI COVID-19 - Gunawan Widjaja (Adiba Aisha Amira, 2024)
The COVID-19 pandemic has changed the paradigm of education systems globally, forcing educational institutions to adapt to distance learning. The role of digital technology in this transition has become key to maintaining educational continuity. With schools and universities closing down, online learning and educational technology (EdTech) are gaining mainstream attention as the primary solution in overcoming physical barriers. Management learning platforms, web conferencing applications and online educational resources are rapidly growing and being used extensively. The results show that while technology has enabled the continuity of learning, there is still a significant digital divide that affects equity in education. Implications of this technology adoption include the need for more adaptive and inclusive education policies and improved infrastructure to support equitable learning. This study concludes that digital technologies are critical in facilitating distance learning during crises and have the potential to improve the quality and affordability of education in the future, provided challenges in access and skills are addressed.